The Effect of Feeding and Feed Hygiene to Oxyurids Infection in Bearded Dragon (Pogona vitticeps) - Indasari, Elly Nur; Budiman, Hafiidh Yahya; Nakita, Agnes Tageomi; Tsabitah, Azmi; Putra, Uray Ade Armanda (Veterinary Biomedical and Clinical Journal, 2024)
Bearded dragons (Pogona vitticeps) are popular exotic pets. Oxyurid can be transmitted to them through contaminated insect and vegetable feed that may carry infective larvae and worm eggs. Oxyuriasis frequently infects Bearded dragon which then causes diarrhea, weight loss, and other digestive issues. This study investigated the impact of various feeding practices and feed hygiene on the prevalence and severity of Oxyurid infections in Bearded dragon. Total of 24 Bearded dragon was used on this study. The variation of feed was used in groups include mixed vegetable and insect feed without hygiene procedures (P0), insect feed without hygiene procedure (P1), vegetable feed without hygiene procedure (P2), mixed vegetable and insect feed with hygiene procedures (P3). For P3, the insects' stomach contents were removed and washed, while the vegetables were rinsed under running water and then dried before being fed to the reptiles. The morphology of Oxyurida eggs found in each group was examined using native and flotation techniques, while, the McMaster technique was carried out for infection intensity measurement. Data observed was analyzed using the Mann-Whitney test to evaluate the significance of the treatment effects, and the Kruskal-Wallis test to examine the associations. It showed that Pharyngodon sp. was found in all feed groups. A significant relationship (P < 0.05) was found between feed type, feed hygiene, and the infection rate of Pharyngodon sp. Conversely, the group which received the same type of feed but adhered to stringent feed hygiene protocols exhibited a significant fewer infection. This study highlights the critical importance of proper feeding management and feed hygiene in maintaining the health of Bearded dragon, particularly in preventing oxyurida infections